2007
DOI: 10.1103/physrevlett.98.166802
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Effect Tuning of Electron-Phonon Coupling in Graphene

Abstract: Gate-modulated low-temperature Raman spectra reveal that the electric field effect (EFE), pervasive in contemporary electronics, has marked impacts on long wavelength optical phonons of graphene. The EFE in this two dimensional honeycomb lattice of carbon atoms creates large density modulations of carriers with linear dispersion (known as Dirac fermions). Our EFE Raman spectra display the interactions of lattice vibrations with these unusual carriers. The changes of phonon frequency and line-width demonstrate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

136
1,205
11
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,117 publications
(1,366 citation statements)
references
References 26 publications
136
1,205
11
14
Order By: Relevance
“…We take λ = 0.03, as obtained from the doping dependence of the G peak frequency [7,8], and we take λ K /λ = 3, as extracted from the ratio of the intensities of the 2D peak at 2700 cm −1 and the 2D peak at 3250 cm −1 [18]. Let us assume the inelastic scattering rate to be dominated by electron-phonon scattering (which is a lower bound), then it can be estimated as γ = (λ + λ K )ω in /8 [19].…”
Section: Discussionmentioning
confidence: 99%
“…We take λ = 0.03, as obtained from the doping dependence of the G peak frequency [7,8], and we take λ K /λ = 3, as extracted from the ratio of the intensities of the 2D peak at 2700 cm −1 and the 2D peak at 3250 cm −1 [18]. Let us assume the inelastic scattering rate to be dominated by electron-phonon scattering (which is a lower bound), then it can be estimated as γ = (λ + λ K )ω in /8 [19].…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, the Raman bands of bulk graphite do not shift after deposition and annealing, which supports the above explanation, as bulk graphite is too thick and is not easily compressed by SiO 2 . Recently, Yan et al [22] and Pisana et al [23] found that the frequency of the G and 2D Raman bands can also be adjusted by charge doping through electron-phonon coupling changes. In addition to the blueshift of the G band, a bandwidth narrowing of ~10 cm 1 was also observed in the case of charge doping.…”
Section: Process-induced Defects and Strain On Graphenementioning
confidence: 99%
“…Because of the very large optical phonon energies in graphene, 24 the dominant cooling mechanism for carriers at low temperatures comes from acoustic phonons. 13 The acoustic phonon cooling in graphene is a fairly weak mechanism which allows carriers to attain temperatures far in excess of that of the lattice, 13,14 and at low temperatures in the Bloch-Grüneisen limit this process is strongly temperature dependent.…”
Section: Maximum Currentsmentioning
confidence: 99%